SELF-ADJUSTMENT OF ADOLESCENTS LIVING WITH STEPFATHER - Faizal Zain Bayu Azagi; Nur'aeni Nur'aeni (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This research aims to analyze the self-adjustment of adolescents living with the stepfather. The research focuses on the self-adjustment of adolescents who live with the stepfather. The research method is qualitative with case study approach. There are two participants, adolescents living with a stepfather, and two informants, the participants family and close friends. Data credibility uses source triangulation, by comparing the obtained data of each source, and technique triangulation, by comparing the obtained data from several different techniques from the same sources. The research result discusses and relates the aspects of self-adjustment with the researchers finding. The result from both participants shows that they can adjust themselves with their new environment, accept and adjust themselves with the situation, have a future vision, and have the ability to face problems.